Vine and soil-based measures of water status in Tempranillo vineyard - Intrigliolo, Diego S.; Castel, Juan R. (Institut für Rebenzüchtung Geilweilerhof (Institute of Grapevine Breeding Geilweilerhof), 2020)
Seasonal changes of leaf and stem water potential and midday stomatal conductance (gs) of Tempranillo grapevines were determined in irrigated and non-irrigated vines in 2003 and 2004. Leaf water potential was measured at pre-dawn (Ψpd) and at midday (Ψl md), while stem water potential was measured in the early morning (Ψs em) and at midday (Ψs md). At Ψpd to -0.54 MPa rain-fed and irrigated vines had similar midday Ψl and Ψs. This was due to both, stomatal closure and reduction of leaf area. Under these conditions, Ψpd and Ψs em were better water stress indicators than midday Ψ. In both years a close correlation was found between Ψpd and Ψs em. However, for a given Ψpd, Ψs em of vines was lower in 2004 than in 2003. This was probably due to the larger leaf area developed by vines in 2004. Stomatal conductance reflected reasonably well differences in the vine water status but its variability was much higher than that of Ψ. Moreover, the afternoon depression of stomatal conductance observed even in irrigated plots, indicates that measuring gs early in the morning is more convenient when assessing different treatments.